Postbariatrische plastische Körperrekonstruktionen - Promny, Theresa; Ludolph, Ingo; Müller-Seubert, Wibke; Cai, Aijia; Promny, Dominik; Horch, Raymund E. (Die Chirurgie, 2024)
Massive weight loss following bariatric surgery is often accompanied by functional impairments due to the resulting excess skin and soft tissues. To achieve both functional reconstruction and restoration of the body silhouette, it is imperative to undergo body contouring surgery involving the strategic transposition of tissues. Several surgical techniques are available for the affected body regions and their application for treatment is determined by the unique circumstances specific to each patient. When conducted by skilled practitioners, postbariatric body reconstruction can be executed safely, leading to outcomes that are both functionally and esthetically satisfying, ultimately contributing to an enhanced quality of life for patients. This article provides the fundamental principles for patient selection, surgical preparation, treatment planning, surgical techniques and the postoperative care following bariatric surgery.
EVALuna2:574356